(3cTa GdfbGH aj aVd CfSGH GdCfLGHs - (3GdHQGbj, GdMSfj, GdfLaj, MqShf, MSjf Hf CMeO Hf GdMSjf Hf ESeGYjd, J (B1332 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdCTjGA dG ef TjA, hchf eG CQGO ef GdcGFfGJ ef ZjQ cjfhfjI(B...(3hLYd fHjgG hgGOjgG hTajYgG CaVd eeG Ndb hCTQa eeG GHJOY(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG bhdg(B: ...(3Ef Gddg CQSd edcG Ydi UhQJc djML Yfc hgh PG jML Yfc aj cd SfIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B233s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B601s
(3cTa GdfbGH aj aVd GdSGOGJ GdCfLGH (B((3GdebOeI(B)(3, hSej NWG aj agQSI cGTa GdZWGA (B((3GdMb GdeHjf aj GdaQb Hjf GdTjYI hGdehGdjf(B) (3hgh cJGH BNQ ZjQ gPG GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs